2016
DOI: 10.2174/1381612822666151210122954
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factor XIIIA (F13A1): Novel Perspectives in Treatment and Pharmacogenetics

Abstract: Factor XIII (FXIII) is a key molecule in the field of blood coagulation and in the last decades it has weakened attention within the field of angiogenesis and tissue repair. FXIII positively influences wound healing in several tissues by exerting multiple plasma and cellular functions. In the field of haemostasis, FXIII cross-links the neo formed fibrin fibers and supports platelet adhesion to the damaged sub-endothelium warranting a solid architecture. In addition, the pro-angiogenic functions of FXIII are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 113 publications
2
33
0
Order By: Relevance
“…Whereas on day 6, it was not differentially expressed. Sixthly, F13A1 is a key molecule, which coagulates the blood and, played role in angiogenesis and tissue repairing when interacts with vascular endothelial growth factor receptor 2 (VEGFR2) and integrin αVβ3 for optimal tissue healing [25]. Seventhly, CCSAP is the only gene which differentially expressed and upregulated on both 2 and 15 days.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas on day 6, it was not differentially expressed. Sixthly, F13A1 is a key molecule, which coagulates the blood and, played role in angiogenesis and tissue repairing when interacts with vascular endothelial growth factor receptor 2 (VEGFR2) and integrin αVβ3 for optimal tissue healing [25]. Seventhly, CCSAP is the only gene which differentially expressed and upregulated on both 2 and 15 days.…”
Section: Discussionmentioning
confidence: 99%
“…Recruited inflammatory cells can remove debris and facilitate the repair process; conversely, unrestrained inflammation inhibits optimal healing leading to adverse events. Moreover, other mediators such as some key coagulation factors might influence innate immunity as well as cell-mediated reactions like healing, response to tissue injury, or inflammatory processes [4, 5]. Overall, as recently suggested, the different immune/inflammatory cell subsets act as messengers implicated in novel inflammatory networks that link different organ systems enlarging the continuum beyond the myocardium and blood vessels in a more integrative pathophysiology standpoint [6].…”
mentioning
confidence: 99%
“…Factor XIII influences wound healing in several tissues, including cardiomyocytes, by exerting multiple plasma and cellular functions. Moreover, the proangiogenic function of factor XIII is directed by the interaction of vascular endothelial growth factor receptor 2 and integrin aVb 3 on the cell membrane [51]. Certain studies showed that low factor XIIIA level correlated with a poor prognosis with regard to MI [52,53].…”
Section: Discussionmentioning
confidence: 99%